Palladium on magnetic Irish moss: A new nano‐biocatalyst for suzuki type cross‐coupling reactions. (8th May 2019) - Dolatkhah, Zahra; Javanshir, Shahrzad; Bazgir, Ayoub; Hemmati, Behnaz
Abstract : A novel heterogeneous magnetic palladium nano‐biocatalyst was designed by utilizing Irish moss, a family of sulfated polysaccharides extracted from algae, as a natural biopolymer. This magnetic Irish moss decorated with palladium (Pd–Fe3 O4 @IM) to form a biomagnetic catalytic system was synthesized and well characterized by FT–IR analysis, X‐ray powder diffraction, field emission scanning electron microscopy, energy‐dispersive X‐ray spectroscopy, atomic absorption spectroscopy and transmission electron microscopy. The catalyst was stable to air and moisture and displayed high catalytic activity in ligand‐free Suzuki–Miyaura cross‐coupling reactions conducted under green chemistry reaction conditions. The aromatic ketones are produced by the cross‐coupling reaction between acid chlorides and aryl boronic acid derivatives in high yields. Abstract : Pd nanoparticles immobilized on magnetic Irish moss, a highly efficient heterogeneous bio‐based catalyst exhibit high catalytic activity and reusability for ligand‐free Suzuki coupling reaction in water. This nano‐biocatalyst is also active toward the cross‐coupling reaction between acid chloride and aryl boronic acid. The resulting catalyst Pd–Fe3 O4 @IM is well characterized by X‐ray powder diffraction, field emission scanning electron microscopy, energy‐dispersive X‐ray spectroscopy, atomic Adsorption analyzer and transmission electron microscopy.